2015
DOI: 10.1177/2373379915601119
|View full text |Cite
|
Sign up to set email alerts
|

Experiential Learning Through Participatory Action Research in Public Health Supports Community-Based Training of Future Health Professionals

Abstract: Engaging community members in research can help cultivate effective partnerships while providing experiential training and continuing education opportunities. Several studies have involved communities in this way, though many have been small in the scale of community involvement or have included little detail of the institutional review board process by which community members became approved researchers in the study. This article presents findings on an evaluation of the training procedures and experiences of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 32 publications
(52 reference statements)
0
7
0
Order By: Relevance
“…Some students would have been exposed to scaling interventions in previous courses; however, this course allowed them to actively engage with these concepts in a concrete manner. Various experiential learning researchers have made reference to individuals applying knowledge and theories learned in coursework, (Cashman & Seifer, 2008; Hu et al, 2016) and gaining exposure to the workplace (Chorazy & Klinedinst, 2019; Marriott et al, 2015; Maudsley & Strivens, 2000; McIntire & DiVito, 2017). Third, we acknowledge that the process leading to entrepreneurial pitching could be strengthened and made more practical as students were not placed in the field.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some students would have been exposed to scaling interventions in previous courses; however, this course allowed them to actively engage with these concepts in a concrete manner. Various experiential learning researchers have made reference to individuals applying knowledge and theories learned in coursework, (Cashman & Seifer, 2008; Hu et al, 2016) and gaining exposure to the workplace (Chorazy & Klinedinst, 2019; Marriott et al, 2015; Maudsley & Strivens, 2000; McIntire & DiVito, 2017). Third, we acknowledge that the process leading to entrepreneurial pitching could be strengthened and made more practical as students were not placed in the field.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, experiential learning is particularly important in the field of global and public health as it provides students with the opportunity to use specific public health theories to address real health challenges (Hu et al, 2016). For example, experiential learning methods have been incorporated into various public health, medicine, nursing, and health-related fields (Marriott et al, 2015). However, studies to date examining experiential learning in public health often focus on service-learning programs that are integrated into the academic curriculum and place a larger emphasis on community engagement (Cauley et al, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…A significant number of primary studies have been conducted on the applications of this intervention to health education. [8] has demonstrated that using participatory based learning programs such as experiential learning can strengthen community research partnerships as well as provide valuable training experiences for current and aspiring health personnel [8]. In addition, [4] found that the reflective writing step of experiential learning can contribute to identifying and addressing of gaps in medical education for resource-limited settings [4].…”
Section: Discussionmentioning
confidence: 99%
“…Negative experiences included a mismatch between community organization and students, as well as time and funding constraints. Community and agency partnerships are an essential component of many ELAs, and like any relationship, they are built on time, trust, and experience (Marriott et al, 2015). These external agencies and community partners are often involved in supervising, training, guiding, or assessing the students on-sites (Marriott et al, 2015).…”
Section: Findings and Connections To Broader Literaturementioning
confidence: 99%